2022
DOI: 10.1016/j.ajog.2021.09.024
|View full text |Cite
|
Sign up to set email alerts
|

An internally validated prediction model for critical COVID-19 infection and intensive care unit admission in symptomatic pregnant women

Abstract: Background Pregnant women are at increased risk of mortality and morbidity due to coronavirus disease 2019 (COVID-19). Many studies reported on the association of COVID-19 with pregnancy specific adverse outcomes but prediction models utilizing large cohort of pregnant women are still lacking for estimating the risk of maternal morbidity and other adverse events. Objective The main aim of this study was to develop a prediction model to quantify the risk of progression t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…In symptomatic pregnant women with COVID-19 in Mexico, the rate of maternal mortality is 1.5% 2 . A recent small cohort of 793 patients from Greece, Turkey, the UK and Austria showed a similar 1.3% incidence of death 25 . However, Zambrano et al 3 described a 0.14% mortality rate in symptomatic pregnant women with SARS-CoV-2 infection in the USA, and Mullins et al 26 found a 0.5% mortality rate in a UK registry and a 0.2% mortality rate in a USA registry, which differ substantially from the rate observed in this study.…”
Section: Comparison With Existing Literaturementioning
confidence: 81%
“…In symptomatic pregnant women with COVID-19 in Mexico, the rate of maternal mortality is 1.5% 2 . A recent small cohort of 793 patients from Greece, Turkey, the UK and Austria showed a similar 1.3% incidence of death 25 . However, Zambrano et al 3 described a 0.14% mortality rate in symptomatic pregnant women with SARS-CoV-2 infection in the USA, and Mullins et al 26 found a 0.5% mortality rate in a UK registry and a 0.2% mortality rate in a USA registry, which differ substantially from the rate observed in this study.…”
Section: Comparison With Existing Literaturementioning
confidence: 81%
“…However, when compared to similar age non-pregnant women, pregnant women have a higher risk of complications-such as severe pneumonia, hospitalizations, admission to an ICU, and invasive mechanical ventilation-and mortality from COVID-19 ( 43 ) . Although there has been a report that severe infection can be seen in the early stages of pregnancy ( 19 ) , late stages of pregnancy are often associated with more severe infection and major unfavorable outcomes ( 44 ) . Similar to the case series of maternal deaths from Iran ( 45 ) maternal deaths in our hospital occurred in the second and third trimesters.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic health records were used to collect information on the demographic and clinical characteristics, obstetric outcomes, and the laboratory results of COVID-19-diagnosed mothers. Some patients in the study cohort had been included in the previous publications ( 19 , 20 , 21 , 22 , 23 ) . The study was approved by the local ethics committee (University of Health Sciences Turkey, Şehit Prof. Dr. İlhan Varank Sancaktepe Training and Research Hospital - no: 2021/218) and by the Ministry of Health COVID-19 Scientific Research Evaluation Commission.…”
Section: Methodsmentioning
confidence: 99%
“…maternal age, body mass index, smoking status, gestational age at diagnosis, number of vaccine doses and comorbidities) were recorded. Maternal age, body mass index and gestational age at infection were treated as potential confounders 9 . The main outcome measures were disease severity at the time of diagnosis and the need for oxygen supplementation.…”
mentioning
confidence: 99%